Study of prenatal and postnatal development of spleen of Gallus domesticus (deshi chicken) - Khalil, Mohsin; Sultana, SZ; Rahman, M; Mannan, S; Ahmed, S; Ara, ZG; Sultana, ZR; Chowdhury, AI (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):169-74. The abstract of this article is available on the PubMed website